Karakteristik Konsumsi Energi, Air dan Nutrisi pada Budidaya Tanaman Bayam Hijau (Amaranthus Hybridus L.) Menggunakan Sistem Fertigasi Deep Flow Technique: Indonesia - Khanisa dilla Khabilah; Sophia Dwiratna; Nurpilihan Bafdal; Kharistya Amaru (Faculty of Agriculture University of Singaperbangsa Karawang, 2022)
Spinach is a vegetable that people like since it owns high nutrition. The high demand for green spinach is not balanced with the amount of production due to the narrowing of agricultural land. Hydroponic spinach cultivation is one of the efforts to solve the problem. Deep Flow Technique (DFT) is a commonly used hydroponic system. The study aimed to examine the characteristics of energy, water, and nutrient consumption on green spinach cultivation as well as the performance of theDFT fertigation system. The study used the analytical descriptive method. The result showed that the energy consumption used was 51.86 during one planting time or the costs incurred for the use of electricity was Rp76.104,64. In addition, water and nutrient consumption used during the planting period was 103.63 liters and 1.504 liters. System performance was viewed in terms of good uniformity with 93% as an average of plant height, 81.75% as the net plant weight, and 80.05% of root length with a faster harvesting time when compared to conventional cultivation namely 22 days. Water use efficiency resulting from the study was 112.127 kg/m3 and 2.82 kg/m2 of land productivity.